Polyethylene compositions and films made therefrom
By developing a polyethylene copolymer containing ethylene and alpha-olefin comonomers and optimizing specific hierarchical structures, the shortcomings of existing LLDPE in sealing temperature and sealing properties are solved, and lower sealing temperatures and higher sealing strengths are achieved.
Patent Information
- Application Number
- CN202380061296.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-22
- Filing Date
- 2023-07-17
- Publication Date
- 2025-04-04
AI Technical Summary
Existing linear low-density polyethylene (LLDPE) requires a high sealing temperature when achieving the required sealing strength and its sealing properties are insufficient.
A polyethylene copolymer was developed that comprises ethylene units and 0.1 mol% to 15% by weight of C3-C18α-olefin comonomer units with a density of 0.900 g/cm3 to 0.915 g/cm3 and a melt index of 0.5 g/10 min to 1.5 g/10 min, and its hierarchical structure was optimized by cross-fractional chromatography and warming rinse grading techniques.
The polyethylene copolymer can improve sealing strength and adhesion while reducing the sealing temperature, improving the sealing properties of the film.
Smart Images

Figure BDA0005280871500000141 
Figure BDA0005280871500000142 
Figure BDA0005280871500000151
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of U.S. Provisional Application No. 63 / 373,154, filed on August 22, 2022, and entitled “Polyethylene Compositions and Films Made Therefrom,” the disclosure of which is incorporated herein by reference in its entirety. Technical Field
[0003] The present disclosure relates to polyethylene polymers, polymerization processes for making such polyethylene polymers, and films made therefrom. Background Art
[0004] Linear low density polyethylene (LLDPE) is a substantially linear polymer consisting of ethylene monomer units and α-olefin comonomer units. Commonly used comonomer units are derived from 1-butene, 1-hexene or 1-octene. LLDPE can be distinguished from conventional low density polyethylene (LDPE) in several ways including different manufacturing methods.
[0005] LLDPE traditionally has good toughness and stiffness, which makes LLDPE useful in packaging materials, such as food packaging materials. However, LLDPE often requires a higher sealing temperature to achieve the required seal strength.
[0006] Some references that may be of interest in this regard include: U.S. Patent Nos. 6,255,426; 7,951,873; 8,247,065; 8,227,564; 8,765,874; 9,718,896; and 10,029,226; and U.S. Patent Publication Nos. US2004 / 0121098; US2007 / 0260016; US2013 / 0266789; US2015 / 0232589; and US2020 / 0339715; and PCT Publication No. WO 2015 / 123164. Summary of the invention
[0007] The present disclosure relates to polyethylene polymers, polymerization processes for making such polyethylene polymers, and films made therefrom.
[0008] For example, the polyethylene copolymer may comprise: ethylene units; and 0.1 mol% to 15 wt% C3-C 18 α-olefin comonomer unit, the polyethylene copolymer has: 0.900 g / cm 3 Up to 0.915g / cm 3density of 0.5 g / 10 min to 1.5 g / 10 min, a melt index (MI, measured according to ASTM D1238-20 at 190° C. and 2.16 kg load) (I2) of 0.5 g / 10 min to 1.5 g / 10 min, a melt index ratio of 15 to 40, a cross-fractional chromatography (CFC) central cross moment covariance of less than -500 K (kg / mol), a CFC correlation of -0.3 or less, a CFC equal halve Tw1-Tw2 of -30° C. or less and a Mw1 / Mw2 of 2 or greater, and a temperature rising elution fractionation (TREF) T75-T25 of 30° C. to 36° C.
[0009] For example, a blown film may comprise: a polyethylene copolymer comprising ethylene units; and 0.1 mol% to 15 wt% of a C3-C 18 α-olefin comonomer unit, the polyethylene copolymer has: 0.900 g / cm 3 Up to 0.915g / cm 3 density, a melt index (MI, measured at 190°C and 2.16 kg load according to ASTM D1238-20) of 0.5 g / 10 min to 1.5 g / 10 min (I2), a melt index ratio of 15 to 40, a cross-fractionation chromatography (CFC) central cross moment covariance of less than -500 K (kg / mol), a CFC correlation of -0.3 or less, a CFC iso-half Tw1-Tw2 of 30°C or less and a Mw1 / Mw2 of 2 or greater, and a temperature rising elution fractionation (TREF) T75-T25 of 30°C to 36°C.
[0010] These and other features and properties of the compositions, methods and articles (eg, films) disclosed herein, as well as their advantageous applications and / or uses, will be apparent from the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] To assist those skilled in the art in making and using the subject matter herein, reference is made to the accompanying drawings. The following figures are included to illustrate certain aspects of the present disclosure and the following figures should not be considered as exclusive configurations. As will occur to those skilled in the art having the benefit of the present disclosure, the disclosed subject matter is capable of considerable modification, alteration, combination and equivalence in form and function.
[0012] The figure is a graph of (Mwl / Mw2) versus (Tw1-Tw2) for the inventive and comparative samples. DETAILED DESCRIPTION
[0013] The present disclosure relates to polyethylene polymers, polymerization methods for preparing such polyethylene polymers, and films prepared therefrom. More specifically, the polyethylene polymers of the present disclosure have reduced density and increased melt index, which advantageously improves the sealing properties of films produced therefrom. For example, the polyethylene polymers of the present disclosure advantageously can maintain toughness properties (e.g., Elmendorf tear) while reducing the temperature required to achieve a seal of a specific strength (e.g., hot tack initiation temperature) and / or increasing the strength of the seal produced within the sealing temperature (e.g., maximum hot tack force).
[0014] definition
[0015] As used herein, "olefins" alternatively referred to as "alkenes" are linear, branched or cyclic compounds of carbon and hydrogen having at least one double bond. For purposes of this specification and the claims thereto, when a polymer or copolymer is referred to as "comprising" an olefin, an olefin unit, or an olefin-derived unit, the olefin present in such a polymer or copolymer is the polymerized form of the olefin. For example, when a copolymer is described as having an "ethylene" content of 35% to 55% by weight, or having 35% to 55% ethylene units, it is understood that the monomer units in the copolymer are derived from ethylene in the polymerization reaction and the derived units are present at 35% to 55% by weight, based on the weight of the copolymer.
[0016] As used herein, the terms "polyethylene polymer", "polyethylene", "ethylene polymer", "ethylene copolymer" and "ethylene-based polymer" mean a polymer or copolymer comprising at least 50 mol% ethylene units, or at least 70 mol% ethylene units, or at least 80 mol% ethylene units, or at least 90 mol% ethylene units, or at least 95 mol% ethylene units or 100 mol% ethylene units (in the case of a homopolymer).
[0017] As used herein, "polymer" may refer to homopolymers, copolymers, interpolymers, terpolymers, and the like. A "polymer" has two or more monomeric units that are the same or different. A "homopolymer" is a polymer having the same monomeric units. A "copolymer" is a polymer having two or more monomeric units that are different from each other. A "terpolymer" is a polymer having three monomeric units that are different from each other. The term "different" used to refer to monomeric units indicates that the monomeric units differ from each other or are isomerically different by at least one atom. Thus, the definition of copolymer, as used herein, includes terpolymers, and the like. Likewise, the definition of polymer, as used herein, includes copolymers, and the like.
[0018] As used herein, a particle having a particle size greater than 0.860 g / cm 3 To less than 0.910g / cm 3Ethylene polymers with a density of 0.910 g / cm 3 Up to 0.925g / cm 3 Ethylene polymers of density of 0.925 g / cm2 are called "linear low density polyethylene" (LLDPE) when they are essentially linear (having little or no long chain branching), which is usually the case with Ziegler-Natta or metallocene-catalyzed PE, or branched low density polyethylene (LDPE) when they are significantly branched (having a high degree of long chain branching), which is usually the case with free radical polymerized PE; 3 Up to 0.940g / cm 3 Ethylene polymers with a density of greater than 0.940 g / cm 3 Ethylene polymers with a density of 1000 Nm are referred to as "high density polyethylene" (HDPE). Density is determined according to ASTM D1505-18. Samples are prepared according to ASTM D4703-16-Appendix 1, Procedure C, and then conditioned according to ASTM D618-21-Procedure A before testing.
[0019] As used herein, and unless otherwise indicated, the term "Cn" means hydrocarbon(s) having n carbon atoms per molecule, where n is a positive integer.
[0020] As used herein, and unless otherwise indicated, the term "hydrocarbon" means a type of compound that contains hydrogen bonded to carbon, and encompasses (i) saturated hydrocarbon compounds, (ii) unsaturated hydrocarbon compounds, and (iii) mixtures of hydrocarbon compounds (saturated or unsaturated), including mixtures of hydrocarbon compounds having different values of n.
[0021] As used herein, the term "film" refers to a continuous, flat (in some cases flexible) polymer structure having an average thickness of 0.1 μm, or 1 μm, or 5 μm, or 10 μm, or 15 μm, or 20 μm to 50 μm, or 75 μm, or 100 μm, or 150 μm, or 200 μm, or 250 μm, or 1000 μm, or 2000 μm, or such a coating of similar thickness adhered to a flexible, non-flexible or solid structure. A "film" can be made of or contain a single layer or multiple layers. Each layer can be made of or contain a polyethylene copolymer of the present disclosure. For example, one or more layers of a "film" can contain a mixture of the disclosed polyethylene copolymers as well as LDPE, additional LLDPE, polypropylene or plastomers.
[0022] As used herein, a composition or film "free of" a component refers to a composition / film that is substantially free of that component, or comprises that component in an amount of less than about 0.01 wt % based on the weight of the total composition.
[0023] Polyethylene copolymer
[0024] The present disclosure provides polyethylene copolymers having a combination of low density and high melt index, maintaining a small amount of long chain branching and a broad orthogonal composition distribution (BOCD) (low Tw1-Tw2 and high Mw1 / Mw2 measured by cross-fractionation chromatography). In addition, the polyethylene copolymers and films thereof can be formed by polymerization and extrusion of commercially desirable polyethylene copolymers, wherein the resulting films have lower seal initiation temperatures and higher adhesion.
[0025] Thus, the polyethylene copolymers of various embodiments herein may exhibit one or more of the following properties:
[0026] 0.900g / cm 3 Up to 0.915g / cm 3 Density in the range, for example from any lower value: 0.900 g / cm 3 , 0.901g / cm 3 , 0.902g / cm 3 , 0.903g / cm 3 , 0.904g / cm 3 , 0.905g / cm 3 , or 0.906 g / cm 3 To the higher of the following values: 0.915 g / cm 3 , 0.914g / cm 3 , 0.913g / cm 3 , 0.912g / cm 3 , 0.911g / cm 3 , 0.910g / cm 3 , or 0.909 g / cm 3 , for example 0.900g / cm 3 Up to 0.914g / cm 3 , alternatively 0.900 g / cm 3 Up to 0.912g / cm 3 , covering any combination from low value to high value (as long as the high end is greater than the low end), for example 0.902 g / cm 3 Up to 0.913g / cm 3Density is measured by ASTM D1505-18, column density, where samples are molded according to ASTM D4703-16, Procedure C, and then conditioned according to ASTM D618-21 (23° ± 2°C and 50 ± 10% relative humidity) for 40 hours before testing density.
[0027] A melt index (MI, also called I2 or I2.16 according to the 2.16 kg load used in the test) greater than 1.0 g / 10 min (ASTM D1238-20, 190°C, 2.16kg), for example, from any of the following low values: 0.5g / 10min, 0.6g / 10min, 0.7g / 10min, 0.8g / 10min, 0.9g / 10min, or 1.0g / 10min to any of the following high ends: 0.9g / 10min, 1.0g / 10min, 1.1g / 10min, 1.2g / 10min, 1.3g / 10min, 1.4g / 10min, or 1.5g / 10min, and the range from any low end to any high end is encompassed herein (as long as the high end is greater than the low end), for example, 0.5g / 10min to 0.9g / 10min, or 0.7g / 10min to 1.5g / 10min, for example, 1.3g / 10min, etc.
[0028] A melt index ratio (MIR, defined as the ratio of I21 / I2 or I21.6 / I2.16, measurement of I21 or HMLI described herein below) in the range from any of the following low values: 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, or 26 to any of the following high values: 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, or 40, with ranges from any of the previous low values to any of the previous high values (e.g., 15 to 27, e.g., 24 to 38, or 27 to 32) contemplated herein.
[0029] Cross fractionation chromatography (CFC) or other semi-analytical methods (described herein below), having (a) a Tw1-Tw2 of -30°C or less, or from any of the following lower values: -40°C, -39°C, -38°C, -37°C, -36°C, or -35°C to any of the following higher values: -33°C, -32°C, -31°C, or -30°C, with ranges from any of the preceding lower values to any of the preceding higher values contemplated herein (as long as the higher end is greater than the lower end) (e.g., -40°C to -30°C, e.g., -37°C to -30°C, or -35°C). -36°C to -31°C) and (b) Mw1 / Mw2 of 2.0 or greater, or from any of the following low values: 2.0, 2.1, 2.2, 2.3, 2.5, 2.5, or 2.6 to any of the following high values: 3.0, 3.1, 3.2, 3.3, 3.4, or 3.5, with ranges from any of the previous low values to any of the previous high values (as long as the high end is greater than the low end) contemplated herein (e.g., 2.0 to 3.5, e.g., 2.4 to 3.5, or 2.5 to 3.2), indicating a broad orthogonal composition distribution (BOCD).
[0030] -500K (kg / mol) or less, or from any lower value of -2200K (kg / mol), -2100K (kg / mol), -2000K (kg / mol), -1900K (kg / mol), or -1800K (kg / mol) to any higher value of -1300K (kg / mol), -1200K (kg / mol), -1100K (kg / mol), -1000K (kg / mol), -900K (kg / mol), -800K (kg / mol), -700K (kg / mol), -6 In some embodiments, the present invention relates to CFC central cross moment covariance (described herein below) within the range of -2200K (kg / mol) to -500K (kg / mol), or -500K (kg / mol), and ranges from any previous lower value to any previous high value (as long as the high end is greater than the low end) are contemplated herein (e.g., -2200K (kg / mol) to -1000K (kg / mol), or -2000K (kg / mol) to -1200K (kg / mol), or -2000K (kg / mol) to -1300K (kg / mol)).
[0031] · A CFC correlation (described herein below) of 2.5 or greater, or in the range of any of the following low values: 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.5, 4.0, 4.5, 5.0, or 5.5 to any of the following high values: 6.0, 6.5, 7.0, 7.5, or 8.0, with ranges from any preceding low value to any preceding high value (so long as the high end is greater than the low end) contemplated herein (e.g., 2.5 to 8.0, e.g., 2.5 to 6.5, or 2.5 to 3.5, or 3.0 to 8.0).
[0032] Temperature Rising Elution Fraction (TREF) T75 minus T25 (T75-T25) (described herein below) from any of the following low values: 30°C, 30.0°C, 30.5°C, or 31.0°C to any of the following high values: 34.0°C, 35.0°C, 35.5°C, or 36°C, with ranges from any of the previous low values to any of the previous high values contemplated herein, e.g., 30°C to 36°C, or 30.0°C to 35.0°C).
[0033] Composition distribution (or comonomer distribution) refers to the distribution of comonomer or short chain branching (SCB) in polymer chains of different lengths (different molecular weights). The ethylene-based polymers of the present disclosure exhibit a relatively constant or uniform distribution of comonomer along chains of different lengths, but there is some variation.
[0034] For example, an ethylene-based polymer can have a composition distribution breadth index (CDBI) ranging from any of the following low values: 30%, 31%, 32%, 33%, 34%, or 35%, or 74% to any of the following high values: 40%, 42%, 42%, 43%, 44%, or 45%, encompassing a range from any of the previous low values to any of the previous high values (e.g., 30% to 45%, or 30% to 40% CDBI). CDBI is defined as the weight percentage of copolymer molecules having a comonomer content within + / - 50% of the median total molar comonomer content (i.e., within + / - 25% of the median), and is referred to, for example, in U.S. Pat. No. 5,382,630. Generally, copolymers with a broader distribution (meaning a greater difference between comonomer incorporation on (i) high molecular weight polymer chains and (ii) low molecular weight polymer chains) result in a lower CDBI, whereas a theoretical copolymer having exactly the same relative comonomer content within + / - 25% of the median length (median molecular weight) in all polymer chains of different lengths should have a CDBI of 100%. The CDBI of a copolymer is readily determined using techniques that separate the individual fractions of a sample of the copolymer. One such technique is to use temperature rising elution fractionation (TREF) to generate a solubility distribution curve, as described in WO 1993003093 (which in turn cites Wild, et al.,J.Poly.Sci., Poly.Phys.Ed. , Vol. 20, p. 441 (1982) and U.S. Pat. No. 5,008,204). All three of the foregoing publications are incorporated herein by reference.
[0035] The data obtained by the TREF technique (e.g., as described in the publication just cited) can be used to first generate a solubility distribution curve for the copolymer. The solubility distribution curve is a graph of the weight fraction of the dissolved copolymer as a function of temperature. This can be converted into a curve of weight fraction versus composition distribution. In order to simplify the correlation of composition to elution temperature, weight fractions less than 15,000 can be ignored. These low weight fractions generally represent insignificant fractions of the ethylene-based polymers disclosed herein.
[0036] Alternatively or additionally, the composition or comonomer distribution can be understood with reference to the T75-T25 values, where T25 is the temperature at which 25% of the eluted polymer is obtained and T75 is the temperature at which 75% of the eluted polymer is obtained, both of which are obtained in the TREF experiment (and a graph plotting the weight percentage of polymer eluted versus the elution temperature) described in US2019 / 0119413 (particularly in paragraphs
[0055] -
[0058] thereof, the description of which is incorporated herein by reference). A narrow distribution is indicated by a relatively small difference in T75-T25 values (and particularly in combination with a high CDBI value), while a broad distribution is reflected in a relatively larger difference in T75-T25 values (and particularly in combination with a smaller CDBI value), meaning a greater difference in crystallinity between fractions of the polymer composition. It is also worth noting that if there is a discrepancy between the actual TREF procedure described in US2019 / 0119413 and the TREF procedures described in WO1993003093, US 5,382,630, and / or US 5,008,204, the TREF procedure described in US2019 / 0119413 should be used. (Also note that the curves generated by the TREF procedure - the solubility distribution curves for CDBI, and the weight fraction eluted versus elution temperature for T75-T25, can have appropriate differences in their generation and CDBI and T75-T25 analysis) Finally, the TREF curves (weight percent polymer eluted versus elution temperature) generated in association with the T75-T25 measurements can be further processed as follows:
[0037] 1. The solvent-only response of the instrument can be generated and subtracted from the TREF curve of the sample. The solvent-only response can be generated by running the same method before the method used to run the polymer sample, but without adding any polymer to the sample bottle; using the same solvent reservoir as the polymer sample and not replenishing with fresh solvent; and running it at a time reasonably close to that of the polymer sample run.
[0038] 2. The temperature axis of the TREF curve can be offset appropriately to correct for the delay in the IR signal caused by the column-to-detector volume. This volume can be found by first filling the injection valve loop with a solution of ~1 mg / ml HDPE resin; then loading the loop volume in the column at the same location where the sample is loaded for TREF analysis; then using an isothermal method to direct the hot solution to the detector at a constant flow rate of 1 ml / min; and then measuring the time after injection that the peak of the HDPE probe appears in the IR signal. The delay volume (ml) is therefore equivalent to the time (min).
[0039] 3. The curve can be baseline corrected and appropriate integration limits can be selected. The curve can be normalized so that the area of the curve is 100 wt%.
[0040] Similarly, known semi-analytical techniques such as cross-fractionation chromatography (CFC) can be used to determine TW1, TW2, Mw1, and Mw2 values. The CFC method and the determination of TW1, TW2, Mw1, and Mw2 are described in U.S. Patent Application Publication No. US2022 / 0048016 (paragraphs 622-634 and Figures 2-3 thereof), which are incorporated herein by reference. As summarized in the public document, Tw1 and Tw2 represent: the average temperature (Tw1) of the polymer eluted in the first half during the CFC experiment and the average temperature (Tw2) of the polymer eluted in the second half, noting that a higher elution temperature infers a higher degree of crystallinity; therefore, the temperatures Tw1 and Tw2 can be used to infer the presence of two clearly crystalline fractions, and the difference between them can be used to infer the difference in the degree of crystallinity between these fractions. Mw1 and Mw2 represent the average weight average molecular weight of the first (Mw1) and second fractions (Mw2) of the eluted polymer, which can be used to infer the relative amounts of less crystalline and more crystalline fractions in the polymer.
[0041] Cross-fractionation chromatography, CFC (also known as TREF-GPC): Cross-fractionation chromatography (CFC) analysis was performed using a CFC-2 instrument from Polymer Char, SA, Valencia, Spain. A general description of the principles of CFC analysis and the specific equipment used is given in the article Ortin, A.; Monrabal, B.; Sancho-Tello, J. Macromol. Symp. 2007, 257, 13. Figure 1 of the preceding article is a suitable schematic diagram of the specific equipment used. An IR4 (Polymer Char) infrared detector is used to generate an absorbance signal proportional to the concentration of polymer in the elution stream. Relevant details of the analytical method and characteristics of the equipment used are as follows.
[0042] The solvent used for preparing the sample solution and for elution was 1,2-dichlorobenzene (ODCB), which was stabilized by dissolving 2 g of 2,6-bis(1,1-dimethylethyl)-4-methylphenol (butylated hydroxytoluene) in a 4 L bottle of fresh solvent at ambient temperature. The sample to be analyzed (50-65 mg) was dissolved in the solvent (25 ml was measured at ambient temperature) by stirring (200 rpm) at 150°C for 75 min. A small volume (0.5 ml) of the solution was introduced into a TREF column (stainless steel; outer diameter, 3 / 8"; length, 15 cm; packed with non-porous stainless steel microspheres) at 150°C, and the column temperature was stabilized at a temperature approximately 20°C higher than the highest temperature fraction (120-125°C) for 30 min to include the GPC analysis in obtaining the final bivariate distribution. The sample volume was then crystallized in the column by decreasing the temperature to an appropriate low temperature (0°C) at a cooling rate of 0.2°C / min. The low temperature was maintained for 10 min, and then the solvent flow was injected (1 ml / min) into the TREF column to elute the soluble fraction (SF) onto a GPC column (3x PLgel 10 μm mixed-B 300x 7.5 mm, Agilent Technologies, Inc.); the GPC oven was kept at high temperature (140°C). SF was eluted from the TREF column for 5 min, and then the injection valve was placed in the "load" position for 40 min to elute all SF through the GPC column (standard GPC injection). All subsequent higher temperature fractions were analyzed using overlapping GPC injections, where the polymer was dissolved for at least 16 min at each temperature step and then the polymer was eluted from the TREF column to the GPC column for 3 min.
[0043] The set point temperatures of these higher temperature fractions are determined by the cumulative curve of the normalized (100 wt %) TREF curves of the same sample. Starting from the temperature of SF, the width of each temperature step is gradually set so that the target 1.5 wt % of the polymer mass will be eluted in the temperature range of the step, as indicated by the TREF cumulative curve. However, because the temperature set point is limited to an integer value, each step is selected before calculating the next higher temperature step so that the polymer mass eluted therein is as close to 1.5 wt % as possible. If the elution is greater than 1.5 wt % in the minimum step size of 1°C, the step size is set to 1°C. If the calculated step size exceeds 10°C, the step size is limited to a maximum of 10°C before calculating the width of the next higher temperature step. When the sum of the polymer mass percentages counted in each step including SF is 100 wt %, the calculation of such a step is completed. In addition, two or more 1°C steps are added to ensure complete elution of the injected polymer. The choice of 1.5 wt% is obtained by aiming for 30-35 fractions (including SF) in the complete CFC analysis of the polymer.The calculation of the order as described above can be done manually or with the help of a computer program.
[0044] The correlation (also referred to herein as the CFC correlation coefficient, or simply the CFC correlation) and covariance (also referred to herein as the central cross-monomer covariance, or the moment of the CFC central cross variance) are mathematically determined from the 2d differential distribution of the weight percent polymer of the same sample as a function of elution temperature and log(M). The 2d differential distribution is obtained in a rectangular coordinate system with temperature on one axis and log(M) on the other. The grid points on the temperature axis range from 0 to 120C and are spaced 1C apart; the grid points on the log(M) axis range from 2 to 8 and are spaced 0.1 units apart. The soluble fraction is not included in the 2d differential distribution, and for any rectangular area element of the grid, the volume under the distribution surface is equal to the weight percent of crystallized polymer eluted over that temperature and log(M) range during the analysis. Correlation and covariance are statistical techniques known to those skilled in the art. See Rice, John (2007), Mathematical Statistics and Data Analysis, Belmont, CA, Brooks / Cole Cengage Learning (e.g., page 138), ISBN 978-0534-39942-9.
[0045] The universal calibration method was used to determine the molecular weight distribution (MWD) and molecular weight average (MWD) of the eluted polymer fraction. n ,M wTwelve narrow molecular weight distribution polystyrene standards in the range of 1.39-3039 kg / mol (obtained from Agilent Technologies, Inc.) were used to generate a universal calibration curve. Mark-Houwink parameters were obtained from Appendix I of Mori, S.; Barth, HG Size Exclusion Chromatography; Springer, 1999. For polystyrene, K = 1.38 x 10 -4 dl / g and α = 0.7; and for polyethylene use K = 5.05 x 10 -4 dl / g and α = 0.693. For polymer fractions eluting at the temperature step with a weight fraction (weight % recovery) of less than 0.5%, MWD and molecular weight average are not calculated; in addition, such polymer fractions are not included in calculating MWD and molecular weight average of the fraction total.
[0046] BOCD indicates that the lower molecular weight polymer chains in the polymer have a high density (e.g., due to the lack of short chain branching (SCB)), while the higher molecular weight fraction has a low density (e.g., due to a greater amount of SCB). Conventional LDPE and LLDPE polymers have longer polymer chains with a higher density than shorter polymer chains, which is a mirror image of the BOCD region. Some LLDPE polymers fall between BOCD and conventional LLDPE and have a uniform but not necessarily narrow MWD (e.g., the Mw1 and Mw2 of the two halves are similar to each other but the MWD within each half can be narrow or broad).
[0047] Polyethylene copolymer can be the polymerization product of ethylene monomer and one or more olefin comonomers, such as alpha-olefin comonomer.Alpha-olefin comonomer can have 3 to 12 carbon atoms, or 4 to 10 carbon atoms, or 4 to 8 carbon atoms.Olefin comonomer can be selected from propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 4-methylpent-1-ene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-hexadecene etc., and any combination thereof, such as 1-butene, 1-hexene, and / or 1-octene.In some embodiments, polyene is used as comonomer. In some embodiments, the polyene is selected from 1,3-hexadiene, 1,4-hexadiene, cyclopentadiene, dicyclopentadiene, 4-vinylcyclohex-1-ene, methyloctadiene, 1-methyl-1,6-octadiene, 7-methyl-1,6-octadiene, 1,5-cyclooctadiene, norbornadiene, ethylidene norbornene, 5-vinylidene-2-norbornene, 5-vinyl-2-norbornene, and olefins formed in situ in the polymerization medium. In some embodiments, the comonomer is selected from isoprene, styrene, butadiene, isobutylene, chloroprene, acrylonitrile and cyclic olefins. In some embodiments, a combination of olefin comonomers is used. In some embodiments, the olefin comonomer is selected from 1-butene and 1-hexene. The olefin comonomer content of the polyethylene copolymer can range from a low of about 0.1 wt%, 5 wt%, 5.5 wt%, 6 wt%, 6.5 wt%, 7 wt%, 7.5 wt%, 8 wt%, 8.5 wt%, 9 wt%, or 10 wt% to a high of about 15 wt%, 13 wt%, 12.5 wt%, 12 wt%, 11.5 wt%, 11 wt%, 10.5 wt%, 10 wt%, 9.5 wt%, or 9 wt%, based on the total weight of monomers in the polyethylene copolymer. The balance of the polyethylene comonomer consists of units derived from ethylene (e.g., from a low of 85%, 88%, 90%, 91%, 92%, 92.5%, 93%, 93.5%, or 94% to a high of 90%, 91%, 92%, 92.5%, 93%, 93.5%, 94%, 94.5%, 95%, 95.5%, 96%, 97%, 99%, or 99.9%). Ranges from any of the preceding low ends to any of the preceding high ends (e.g., 88% to 93%, such as 85% to 90% ethylene-derived units and the balance olefin comonomer-derived content) are contemplated herein.
[0048] Polyethylene copolymer can also have high load melt index (HLMI) (also referred to as I21 or I21.6 according to the 21.6kg load used in the test), which is from the following low value: 5g / 10min, 10g / 10min, 15g / 10min, 20g / 10min, 25g / 10min, or 30g / 10min to the following high value: 35g / 10min, 40g / 10min, 45g / 10min, or 50g / 10min in the range. The scope of any previous low value to any previous high value is contained herein (e.g., 5g / 10min to 50g / 10min, e.g., 15g / 10min to 50g / 10min, or 20g / 10min to 40g / 10min). The term "high load melt index" ("HLMI") is the grams extruded in 10 minutes under the effect of a standard load (21.6kg) and is an inverse measure of viscosity. As provided herein, HLMI (I21) is determined according to ASTM D1238-20 (190° C. / 21.6 kg) and is sometimes also referred to as I21 or I21.6.
[0049] The polyethylene copolymer may also have a molecular weight distribution (MWD) of about 3.7 to about 4.3. The MWD may also be in the range of from the following low values: about 3.7, 3.8, or 3.9 to the following high values: about 3.9, 4.0, 4.1, 4.2, or 4.3, covering the range from any previous low value to any previous high value, as long as the high end of the range is greater than the low end. The MWD is defined as the weight average molecular weight (Mw) divided by the number average molecular weight (Mn).
[0050] The weight average molecular weight (Mw) of the polyethylene copolymer of various embodiments can be in the range of 100,000 g / mol to 150,000 g / mol, such as 100,000 g / mol to 125,000 g / mol, such as 110,000 g / mol to 140,000 g / mol, or 125,000 g / mol to 150,000 g / mol, covering the range from any previous lower end to any previous high end.
[0051] The number average molecular weight (Mn) of the polyethylene copolymer of various embodiments can be in the range of 24,000 to 38,000 g / mol, such as 24,000 to 30,000 g / mol, such as 26,000 to 35,000 g / mol, such as 30,000 to 38,000 g / mol, covering the range from any previous lower end to any previous high end.
[0052] The Z-average molecular weight (Mz) of the polyethylene copolymers of various embodiments can be in the range of 230,000 to 380,000 g / mol, e.g., 230,000 to 320,000 g / mol, or 250,000 to 350,000 g / mol, e.g., 290,000 to 380,000 g / mol, covering ranges from any of the previous low ends to any of the previous high ends (e.g., 230,000 to 350,000 g / mol or 25,000 to 380,000 g / mol).
[0053] The short chain branching of the polyethylene copolymers of various embodiments may be in the range of 20 branches / 1000C to 25 branches / 1000C.
[0054] The distribution and moment of molecular weight (Mw, Mn, Mw / Mn, etc.), branching index (g'vis) and short chain branching were determined by using a high temperature gel permeation chromatography (Polymer Char GPC-IR) equipped with an infrared detector IR5 based on a multi-channel bandpass filter, an 18-angle Wyatt Dawn Heleos light scattering detector and a 4-capillary viscometer with a Wheatstone bridge configuration. Three Agilent PLgel 10-μm mixed-B LS columns were used to provide polymer separation. Aldrich reagent grade 1,2,4-trichlorobenzene (TCB) with 300ppm antioxidant butylated hydroxytoluene (BHT) was used as the mobile phase. The TCB mixture was filtered through a 0.1-μm Teflon filter and degassed using an online degasser before the TCB mixture entered the GPC instrument. The nominal flow rate was 1.0mL / min and the nominal injection volume was 200μL. The entire system including the transfer line, column and viscosity detector was contained in an oven maintained at 145°C. Weigh the polymer sample and seal it in a standard bottle to which 80-μL flow marker (heptane) is added. After the bottle is loaded into the autosampler, the polymer is automatically dissolved in the instrument with 8mL of added TCB solvent. Shake continuously at 160°C for about 2 hours to dissolve the polymer. The concentration (c) at each point of the chromatogram can be calculated by the IR5 broadband signal intensity (I) minus the baseline, using the following equation: c=βI, where β is the mass constant. The mass recovery is calculated by the ratio of the integral area of the concentration chromatography in the elution volume and the injection mass (which is equal to the predetermined concentration multiplied by the injection loop volume). Conventional molecular weight (IR MW) is determined by combining universal calibration relationships with column calibration (which is carried out using a series of monodisperse polystyrene (PS) standards ranging from 700 to 10 million grams / mol). The MW at each elution volume is calculated using the following equation:
[0055]
[0056] The variables with the subscript "PS" represent polystyrene, while those without the subscript represent the test sample. PS =0.67 and K PS =0.000175, while for ethylene-hexene copolymers, α and K are calculated by empirical equations (Sun, T. et al., Macromolecules 2001, 34, 6812), where a=0.695 and K=0.000579 (1-0.75 Wt), where Wt is the weight fraction of the hexane comonomer. It should be noted that the comonomer composition is determined by the ratio of the IR5 detector intensities corresponding to the CH2 and CH3 channels calibrated using a series of PE and ethylene-hexene homopolymer / copolymer standards (whose nominal values are predetermined by NMR or FTIR). Here the concentration is in g / cm 3 The molecular weight is expressed in g / mol, and the intrinsic viscosity (and hence K in the Mark-Houwink equation) is expressed in dL / g.
[0057] The comonomer composition is determined by the ratio of the IR5 detector intensities corresponding to the CH2 and CH3 channels calibrated using a series of PE and PP homopolymer / copolymer standards (whose nominal values are predetermined by NMR or FTIR). In particular, this provides the number of methyl groups per 1000 total carbons (CH3 / 1000TC) (or branches / 1000C) as a function of molecular weight. The amount of short chain branching (SCB) per 1000TC as a function of molecular weight (SCB / 1000TC) is then calculated by applying a chain end correction to the CH3 / 1000TC function, assuming that each chain is linear and terminated by a methyl group at each end.
[0058] The LS molecular weight (M) at each point in the chromatogram was determined by analyzing the LS output using the Zimm model for static light scattering.
[0059]
[0060] Here, ΔR(θ) is the excess Rayleigh scattering intensity measured at the scattering angle θ, c is the polymer concentration determined by IR5 analysis, A2 is the second virial coefficient, P(θ) is the shape factor of the monodisperse random coil, and Ko is the optical constant of the system:
[0061]
[0062] Where N Ais Avogadro's constant, and (dn / dc) is the refractive index increment of the system. The refractive index of TCB at 145°C and λ=665nm is n=1.500. For purposes of this disclosure and the claims thereto, ethylene-hexene copolymers have (dn / dc)=0.1048.
[0063] The specific viscosity is determined using a high temperature Polymer Char viscometer, which has four capillaries arranged in a Wheatstone bridge configuration with two pressure sensors. One sensor measures the total pressure drop across the detector, and the other, located between the two sides of the bridge, measures the differential pressure. The specific viscosity η of the solution flowing through the viscometer is calculated from their outputs S The intrinsic viscosity [η] at each point in the chromatogram was calculated by the equation [η] = ηs / c, where c is the concentration and was determined from the IR5 broadband channel output.
[0064] Branching coefficient (g' vis ) is calculated using the output of the GPC-IR5-LS-VIS method as follows. The average intrinsic viscosity [η] of the sample avg Calculated by the following formula:
[0065]
[0066] where the sum is taken from all chromatographic slices i between the integration limits. Branching coefficient g' vis Defined as: Among them, M v is the viscosity average molecular weight based on molecular weight determined by LS analysis, and K and α are to a reference linear polymer, which for purposes of this disclosure and claims thereto, α and K are the same as described above for linear polyethylene polymers.
[0067] In addition, the polyethylene copolymer can have a complex shear viscosity (η*) at 0.01 rad / sec and 190°C in the range of 5000 Pa·s to 19000 Pa·s; or from any of the following lower values: 5000 Pa·s; 6000 Pa·s; 7000 Pa·s; 8000 Pa·s; 9000 Pa·s; 10000 Pa·s; or 11000 Pa·s to any of the following higher values: 12000 Pa·s; 13000 Pa·s; 14000 Pa·s; 15000 Pa·s; 16000 Pa·s; 17000 Pa·s; 18000 Pa·s; or 19000 Pa·s, covering a range from any low end to any high end (e.g., 6000 to 8000 Pa·s).
[0068] The complex shear viscosity (η*) at 100 rad / sec and 190°C can be in the range of 1300 Pa·s to 2500 Pa·s; for example, from any of the following lower values: 1300 Pa·s; 1400 Pa·s; 1500 Pa·s; or 1600 Pa·s to any of the following higher values: 2100 Pa·s; 2200 Pa·s; 2300 Pa·s; 2400 Pa·s; or 2500 Pa·s, covering a range from any previous lower value to any previous higher value (e.g., 1500 to 2300 Pa·s).
[0069] In some embodiments, the polyethylene copolymer has a shear thinning ratio (η* at 0.01 / 100) of less than 10, or in the range of 3 to 10, or 4 to 9, or 4 to 8.
[0070] Rheological data such as "complex shear viscosity (η*)" reported in Pascal seconds can be measured at 0.01 rad / sec and 100 rad / sec. Complex shear viscosity and other rheological measurements can be obtained from small angle oscillatory shear (SAOS) experiments. For example, a rotational rheometer such as Advanced Rheometrics Expansion System (ARES-G2 model) or Discovery Hybrid Rheometer (DHR-3 model) can be used to measure complex shear viscosity using parallel plates (diameter = 25 mm) in dynamic mode under a nitrogen atmosphere. The rheometer can be thermally stabilized at 190°C for at least 20 minutes, and then the compression molded sample is inserted into the parallel plates. In order to determine the viscoelastic behavior of the sample, a frequency scan in the range of 0.01 to 628 rad / s can be performed at a temperature of 190°C under a constant strain that does not affect the measured viscoelastic properties. The scanning frequency is equidistant on a logarithmic scale so that 5 frequencies are detected every ten. Depending on the molecular weight and temperature, a strain of 3% can be used and the linearity of the response has been confirmed. A nitrogen stream was circulated through the oven to minimize chain growth or crosslinking during the experiment. Samples can be compression molded at 190°C without stabilizers. Sinusoidal shear strain can be applied. Shear thinning slope (STS) can be measured using a plot of the logarithm (base ten) of the dynamic viscosity versus the logarithm (base ten) of the frequency. The slope is the frequency 100s -1 log(dynamic viscosity) and frequency 0.01s at -1 The difference in log(dynamic viscosity) at ω is divided by 4. The complex shear viscosity (η*) versus frequency (ω) curve can be calculated using the Carreau-Yasuda model: η*-η ∞ =(η 0- η ∞ )*(1+(λω) a ) (n-1) / a To fit.
[0071] The five parameters in the model are: η0, the zero shear viscosity; λ, the relaxation time; and n, the power law exponent; η ∞ , infinite rate viscosity; and a, conversion index. Zero shear viscosity is the value at the plateau in the Newtonian region of the flow curve at low frequencies, and the dynamic viscosity at this plateau is independent of frequency. The relaxation time corresponds to the inverse of the frequency at which shear thinning begins. The power law exponent describes the degree of shear thinning, which is due to the fact that the magnitude of the slope of the flow curve at high frequencies on the log(η*)-log(ω) graph approaches n-1. For Newtonian fluids, n=1 and the dynamic complex viscosity is independent of frequency.
[0072] The "shear thinning ratio," reported as a unitless number, is represented by the decrease in complex viscosity as the shear rate increases. Herein, shear thinning may be determined as the ratio of the complex viscosity at a frequency of 0.01 rad / s to the complex viscosity at a frequency of 100 rad / s.
[0073] The solubility distribution breadth index (SDBI) is used as a measure of the breadth of the solubility distribution curve for a given polymer.The procedure used herein to calculate the SDBI is as described in PCT Patent Application WO 93 / 03093, published February 18, 1993, pages 16-18.
[0074] The SDBI of the polyethylene copolymers of various embodiments may be in the range of 21.0°C to 25.0°C, or 21.0°C to 24.5°C, or 22.0°C to 24.5°C.
[0075] Waste Processing Olefins
[0076] Processing of waste materials, such as plastic waste, can result in the production or recovery of olefins, or attribution of waste raw materials to olefins, including any alpha-olefin disclosed herein for use in making polymer compositions disclosed herein (e.g., polyethylene copolymers). Waste materials can include plastic waste obtained from any source, including but not limited to urban, industrial, commercial or consumer sources. Plastic waste can also be obtained from common sources or from mixed sources, including mixed plastic waste obtained from urban or local sources and / or from waste streams of PET, HDPE, LDPE, LLDPE, polypropylene and / or polystyrene. In addition, waste materials can include thermoplastic elastomers and thermosetting rubbers, such as from tires and other products made of natural rubber, polybutadiene, styrene-butadiene, butyl rubber and EPDM.
[0077] The waste materials processed may also include any of a variety of polymeric and non-polymeric articles used without limitation. Some examples of many types of polymeric articles may include: films (including cast films, blown films and other films), sheets, fibers, woven and non-woven fabrics, furniture (e.g., garden furniture), sports equipment, bottles, food and / or liquid storage containers, transparent and translucent articles, toys, tubes and pipes, sheets, packages, bags, sacks, coatings, covers, seals, boxes, trays, cups, non-food containers, barrels, insulating materials, and / or medical devices. Additional examples include automotive, aviation, marine and / or water transport components (e.g., bumpers, grilles, decorative parts, instrument panels, instrument panels, etc.), cables and cable sheaths, agricultural films, geomembranes, playground equipment and other such articles, whether blow molded, spin-molded, injection molded or otherwise. Any of the foregoing may include polymeric and non-polymeric articles (e.g., packaging or other articles may include inks, cardboard, paper, metal deposits, etc.). One of ordinary skill will appreciate that such polymeric articles can be made from any of a variety of polymeric and / or non-polymeric materials, and that the polymeric materials can vary widely (e.g., ethylene-based, propylene-based, butyl-based polymers and / or any C2 to C 40 or even higher olefins, and also include polymers based on any one or more types of monomers, such as C2 to C 40 Common examples include ethylene, propylene, butene, pentene, hexene, heptene, and octene; and polyene (including cyclic olefin) monomers such as ethylidene norbornene (ENB) and vinylidene norbornene (VNB) (including, for example, when such cyclic olefins are used as comonomers, such as with ethylene monomers).
[0078] Processing of waste materials, such as by pyrolysis of plastic waste, can directly produce or recover olefins for making such polymer compositions or via attribution of the use of waste materials as feed to the system, such as by accounting for, allocating, and / or offsetting or replacing other hydrocarbons in the mass or energy balance of the system, such as determined by third-party certification involving circularity. Polymers certified for circularity by third-party certification can be referred to as certified recyclates. An example of such certification is the mass balance chain of the regulatory approach proposed by International Sustainable Development and Carbon Certification.
[0079] Various methods may be employed to produce, recover or attribute olefins for use in the polymers disclosed herein. For example, olefins may be obtained from or in connection with co-processing of waste materials (e.g., plastic waste) with other hydrocarbon feeds in a cracking, coking, hydrotreating and / or cracking process. For example, olefins may be produced from or in connection with a fluid catalytic cracking unit, delayed coking unit, fluid coking unit (including FLEXICOKING TMDevice), hydrotreating device (including hydrocracking and hydrotreating device), and / or steam cracking device (including gas or liquid steam cracking device) directly or indirectly. Alternatively, such a device may receive the pyrolysis product of the processing of such waste (such as separated or combined recycled pyrolysis gas and / or recycled pyrolysis oil) as feed or co-feed. Olefins can be produced directly by such a method or by further processing, such as separation, treatment, and / or cracking of the effluent of such a method to obtain olefins. As an example, olefins can be obtained by processing recycled pyrolysis oil and / or recycled pyrolysis gas produced by pyrolysis of plastic waste. "Recycled pyrolysis oil" as used herein refers to a substance composition that is liquid when measured at 25°C and 1atm, and at least a portion of it is obtained by pyrolysis of recycled waste (e.g., recycled plastic waste). "Recycled pyrolysis gas" as used herein refers to a substance composition that is gaseous at 25°C and 1atm, and at least a portion of it is obtained by pyrolysis of recycled waste. In addition, waste materials such as plastic waste are used as feed materials for fluid catalytic cracking units, delayed coking units, fluid coking units (including FLEXICOKING TM Co-processing of feeds or co-feeds to a hydroprocessing unit (including hydrocracking and hydrotreating units), a hydrotreating unit (including gas or liquid steam cracking units), and / or a steam cracking unit (including gas or liquid steam cracking units) can result in attribution of the waste materials to the olefins, polymers or polymer compositions described herein, such as by accounting for, allocating, and / or offsetting or replacing other hydrocarbons in the mass or energy balance of the system, such as based on third-party certification related to circularity.
[0080] Therefore, the method according to various embodiments of the present invention may further include obtaining olefins that have been produced or recovered by processing of plastic waste or olefins (processing of plastic waste has been attributed to the olefins), for example, for use in the polymerization method described elsewhere herein; and the polymer composition (e.g., polyethylene copolymer) of various embodiments described herein may include olefins that have been produced or recovered by processing of plastic waste or olefins (processing of plastic waste has been attributed to the olefins). As an example, at least a portion of the olefin content (e.g., used in the method and / or included in the composition described herein) can come from olefins directly produced or recovered by processing of plastic waste. Similarly, the processing of plastic waste can be attributed to at least a portion of the olefins (e.g., used in the method and / or included in the composition described herein).
[0081] Blends and Additives
[0082] In some embodiments, polyethylene copolymers can be formulated (e.g., blended) with one or more other polymer components. In some embodiments, these other polymer components are alpha-olefin polymers such as polypropylene or polyethylene homopolymers and copolymer compositions. In some embodiments, these other polyethylene polymers are selected from linear low density polyethylene, high density polyethylene, medium density polyethylene, low density polyethylene, and other differentiated polyethylene.
[0083] In some embodiments, the formulated blend may contain additives, which are determined based on the final use of the formulated blend. In some embodiments, the additives are selected from fillers, antioxidants, phosphites, anti-stick additives, tackifiers, UV stabilizers, heat stabilizers, anti-blocking agents, mold release agents, antistatic agents, pigments, colorants, dyes, waxes, silica, process aids, neutralizers, lubricants, surfactants and nucleating agents. In some embodiments, the additives are present in an amount of 0.1 ppm to 5 wt%.
[0084] The polyethylene copolymers of the present disclosure may optionally be blended with one or more process aids to form a polyethylene blend. Due to the improved properties of the polyethylene copolymers of the present disclosure, advantageously, such process aids may even be omitted in blown films (e.g., films of some embodiments, and in particular blown films, may be free of or substantially free of polymeric process aids, and in particular polymeric process aids containing fluorine; wherein "substantially free" means free of any intentionally added components, but allowing up to 100 ppm of such component(s) as impurities).
[0085] Aggregation methods
[0086] The polymerization process preferably comprises a gas phase polymerization, and in particular a fluidized bed gas phase polymerization. The gas phase polymerization can be carried out in any suitable reactor system, such as a stirred- or paddle-type reactor system. For a discussion of suitable gas phase fluidized bed polymerization systems well known in the art, see U.S. Pat. Nos. 7,915,357; 8,129,484; 7,202,313; 6,833,417; 6,841,630; 6,989,344; 7,504,463; 7,563,851; and 8,101,691.
[0087] In such a polymerization process, a gas phase fluidized bed process is carried out by continuously passing a stream containing ethylene and olefin comonomers through a fluidized bed reactor at a speed sufficient to keep a bed of solid particles in a suspended state under reaction conditions and in the presence of a catalyst composition. A stream containing unreacted ethylene and olefin comonomers (which may be referred to as a "cycle gas" stream) is continuously extracted from the reactor, the stream is compressed, cooled, optionally partially or completely condensed, and recycled back to the reactor. The prepared polyethylene copolymer is extracted from the reactor and will be added to the recycle stream instead of ethylene and olefin comonomers. In some embodiments, a gas inert to the catalyst composition and reactants is present in the gas stream.
[0088] The circulating gas may contain an induced condensing agent (ICA). ICA is one or more non-reactive alkanes that can be condensed in the polymerization process to remove the heat of reaction. In some embodiments, the non-reactive alkanes are selected from C1-C5 alkanes, such as propane, butane, isobutane, pentane, isopentane, hexane and one or more of their isomers and derivatives. In some cases, a mixture of two or more such ICAs (e.g., propane and pentane, propane and butane, butane and pentane, etc.) may be particularly desired. The operation of a gas-phase fluidized bed reactor using an ICA can be carried out in a "dry mode" (the concentration of total ICA relative to the total circulating gas is generally less than 5 mol%), or in a "condensing" or "condensed" mode in the case of higher ICA concentrations.
[0089] The polymerization process can be carried out in the substantial absence of catalyst poisons such as moisture, oxygen, carbon monoxide and acetylene. However, it is noted that oxygen can be added back into the reactor to alter the polymer structure and the performance characteristics of the polymer.
[0090] In addition, organometallic compounds may be used as scavengers to remove catalyst poisons, thereby increasing catalyst activity, or for other purposes. Auxiliary agents may additionally or alternatively be used in the process. Similarly, hydrogen may be added to affect polymer molecular weight and distribution.
[0091] A continuous cycle is often used, in which the first part of the reactor cycle, the circulating gas stream, or recycle stream or fluidizing medium, is heated in the reactor by the heat of polymerization. This heat is removed in the second part of the cycle by a cooling system outside the reactor.
[0092] Reactor pressure can vary from 100 psig (680 kPag) to 500 psig (3448 kPag), or in the range of 200 psig (1379 kPag) to 400 psig (2759 kPag), or in the range of 250 psig (1724 kPag) to 350 psig (2414 kPag). In some embodiments, the reactor is operated at a temperature in the range of 60°C to 120°C, 60°C to 115°C, 70°C to 110°C, 70°C to 95°C, or 85°C to 95°C.
[0093] The mole percent of ethylene can be 25.0-90.0 mole percent, or 50.0-90.0 mole percent, or 70.0-85.0 mole percent, and the ethylene partial pressure is in the range of 75 psia (517 kPa)-300 psia (2069 kPa), or 100-275 psia (689-1894 kPa), or 150-265 psia (1034-1826 kPa), or 200-250 psia (1378-1722 kPa). The ethylene concentration in the reactor may also be 35-95 mol%, such as in the range of from a low of 35, 40, 45, 50, or 55 mol% to a high of 70, 75, 80, 85, 90, or 95 mol% and further wherein the ethylene mol% is measured based on the total moles of gas in the reactor (including, if present, ethylene and / or comonomer gas and inert gases such as nitrogen, isopentane or one or more of the other ICA(s), etc.); in terms of vol-ppm hydrogen, the measurement may be made in the recycle gas outlet rather than in the reactor itself for convenience. The comonomer concentration may range from 0.2-1.0 mol%, such as in the range of from a low of 0.2, 0.3, 0.4 or 0.5 mol% to a high of 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95, or 1.0 mol%.
[0094] catalyst
[0095] The catalyst employed in the polymerization may be a metallocene catalyst. In particular, the metallocene catalyst may be selected from the catalysts described in US Pat. No. 6,956,088, which is incorporated herein by reference for all purposes.
[0096] Manufactured products
[0097] The polyethylene copolymer described herein can be blown into a film, more specifically, extruded by an annular die in a molten state and then blown and cooled to form a tubular blown film, which can then be cut axially and unfolded to form a flat film. More specifically, blown film can be prepared as follows. The polymer composition is introduced into the feed hopper of an extruder (e.g., water-cooled, resistance-heated, and a 50mm extruder with an L / D ratio of 30:1). A 28cm die can be used to produce a film with a 1.4mm die gap and double air rings and inner bubble cooling. The film is extruded into a film through a die, and the film is cooled by air blown onto the surface of the film. The film is taken out from the die, generally a cylindrical film is formed, cooled, collapsed, and optionally required auxiliary processes are carried out, such as cutting, processing, sealing or printing. Common melting temperatures are from about 180°C to about 230°C. The blown film rate is generally about 3 to about 25 kg / hour / inch die circumference (about 4.35 to about 26.11 kg / hour / cm die circumference). The finished film can be wound into a roll for subsequent processing. Illustrative blown film methods and equipment suitable for forming films according to embodiments of the present invention are described in U.S. Patent No. 5,569,693.
[0098] The resulting film has an excellent balance of mechanical properties, toughness, sealability and tack / adhesion properties. The film can also be used for shrink film and form fill and seal applications that require resistance to mechanical damage. The film also has good flexibility / tactile and optical / transparency properties, which is useful for food packaging at any temperature.
[0099] The seal initiation temperature of the blown film comprising the described polyethylene copolymer can be 80°C or less, or 75°C or less, or in the range of 65°C to 80°C, e.g., 65°C to 75°C, or 70°C to 80°C. The seal initiation temperature is determined using a 1 inch film strip of 1 mil gauge sealed at 73 psi (0.5 N / mm2) for 1 second at various temperatures. After 40 hours of ASTM conditioning at 23°±2°C and 50±10% relative humidity, the sealed samples are tested in T-joint peel mode at a pull speed of 20 inches / minute. The seal initiation temperature is the first temperature at which a force of 4N or more is required to pull the sample apart.
[0100] The hot tack initiation temperature of the blown film comprising the described polyethylene copolymer can be 90°C or less, or 70°C to 90°C, or 70°C to 87°C, or 75°C to 87°C, or 75°C to 85°C. The hot tack initiation temperature is used at 73 psi (0.5 N / mm 2The hot tack initiation temperature is determined by sealing a 1 inch film strip of 1 mil film thickness for 0.5 seconds at various temperatures (unless otherwise indicated, it is a temperature of 60°C to 130°C in intervals of 5°C). After a 0.4 second delay, the sealed sample is pulled at 200 mm / speed in a T-joint peel mode. The hot tack initiation temperature is the first temperature at which a force of 5 N / 25 mm or more is required to pull the sample apart.
[0101] The maximum hot tack of a blown film comprising the described polyethylene copolymers may be 13 N / 25 mm or greater, or in the range of 13 N / 25 mm to 22 N / 25 mm, e.g., 13 N / 25 mm to 20 N / 25 mm, or 17 N / 25 mm to 22 N / 25 mm. The maximum hot tack is used at 73 psi (0.5 N / mm 2 ) at various temperatures for 0.5 seconds. After a 0.4 second delay, the sealed sample is pulled at 200 mm / speed in T-joint peel mode. The maximum hot tack is the maximum force that the sample can withstand over the entire tested temperature range (unless otherwise indicated, it is 60°C to 130°C in 5°C intervals) in N / 25mm.
[0102] The machine direction (MD) 1% secant modulus (ASTM D882-18, using 1 inch by 7 inch tape) of blown films comprising the described polyethylene copolymers can range from 17,000 psi to 25,000 psi, eg, from 17,000 psi to 21,000 psi, or from 19,000 psi to 25,000 psi.
[0103] The transverse direction (TD, 90° to MD in the plane of the film) 1% secant modulus (ASTM D882-18, using a 1 inch by 7 inch tape) of blown films comprising the described polyethylene copolymers can be in the range of 18,000 psi to 35,000 psi, e.g., 18,000 psi to 25,000 psi, or 20,000 psi to 30,000 psi, or 25,000 psi to 35,000 psi.
[0104] Blown films comprising the described polyethylene copolymers may have MD yield strength (ASTM D D882-18, using 1 inch by 4 inch tapes) in the range of 900 psi to 1300 psi, e.g., 900 psi to 1200 psi, or 1000 psi to 1300 psi.
[0105] The TD yield strength (ASTM D882-18, using 1 inch by 4 inch tape) of blown films comprising the described polyethylene copolymers can range from 900 psi to 1500 psi, eg, from 900 psi to 1300 psi, or from 1100 psi to 1500 psi.
[0106] Blown films comprising the described polyethylene copolymers may have MD tensile break strength (ASTM D882-18, using 1 inch by 4 inch tapes) in the range of 7000 psi to 10000 psi, e.g., 7000 psi to 9000 psi, or 8000 psi to 10000 psi.
[0107] Blown films comprising the described polyethylene copolymers may have a TD tensile break strength (ASTM D882-18, using a 1 inch by 4 inch tape) in the range of 7000 psi to 10000 psi, eg, 7000 psi to 9000 psi, or 8000 psi to 10000 psi.
[0108] Blown films comprising the described polyethylene copolymers may have MD elongation at break (ASTM D882-18, using 1 inch by 4 inch tapes) in the range of 250% to 600%, eg, 250% to 400%, or 350% to 600%.
[0109] Blown films comprising the described polyethylene copolymers may have a TD elongation at break (ASTM D882-18, using 1 inch by 4 inch tapes) in the range of 250% to 600%, eg, 250% to 400%, or 350% to 600%.
[0110] Blown films comprising the described polyethylene copolymers may have MD elongation at yield (ASTM D882-18, using 1 inch by 4 inch tapes) in the range of 5.5% to 7.5%, eg, 5.5% to 7.0%, or 6.0% to 7.5%.
[0111] Blown films comprising the described polyethylene copolymers may have a TD elongation at yield (ASTM D882-18, using 1 inch by 4 inch tapes) in the range of 5.5% to 7.5%, eg, 5.5% to 7.0%, or 6.0% to 7.5%.
[0112] The MD Elmendorf Tear (ASTM D1922-15, conditioned at 23°±2°C and 50±10% relative humidity for 40 hours) of blown films comprising the described polyethylene copolymers can be 200 g / mil or greater, or 250 g / mil or greater, or 300 g / mil or greater. Or in the range of 200 g / mil to 400 g / mil, or 250 g / mil to 400 g / mil, or 300 g / mil to 400 g / mil. The unit g / mil can be converted to kN / m, where 1 g / mil=0.392 kN / m. Blown films comprising the described polyethylene copolymers may have an MD Elmendorf Tear of 75 kN / m or greater, or 100 kN / m or greater, or in a range of 75 kN / m to 175 kN / m, or 75 kN / m to 125 kN / m, or 100 kN / m to 175 kN / m.
[0113] The TD Elmendorf Tear (ASTM D1922-15, conditioned at 23°±2°C and 50±10% relative humidity for 40 hours) of blown films comprising the described polyethylene copolymers can be 250 g / mil or greater, or 300 g / mil or greater, or in the range of 250 g / mil to 450 g / mil, or 300 g / mil to 450 g / mil, or 350 g / mil to 450 g / mil. The TD Elmendorf Tear of blown films comprising the described polyethylene copolymers can be 110 kN / m or greater, or 120 kN / m or greater, or in the range of 110 kN / m to 170 kN / m, or 110 kN / m to 150 kN / m, or 140 kN / m to 170 kN / m.
[0114] The dart drop (ASTM D1709-16, Phenolic, Method A) of blown films comprising the described polyethylene copolymers can be in the range of 500 g / mil to 1200 g / mil, or 500 g / mil to 1000 g / mil, or 700 g / mil to 1200 g / mil. The dart drop (ASTM D-1709, Phenolic, Method A) of blown films comprising the described polyethylene copolymers can be in the range of 200 kN / m to 500 kN / m, or 200 kN / m to 400 kN / m, or 300 kN / m to 500 kN / m.
[0115] The peak puncture force (ASTM D5748-19, using a 3 / 4 inch stainless steel uncoated probe and two 0.25 mil HDPE slides, machine model United SFM-1, test speed 10 in / min) can be in the range of 10.5 pounds force / mil (lbf / mil) to 14.0 lbf / mil, or 10.5 lbf / mil to 13.5 lbf / mil, or 11.0 lbf / mil to 14.0 lbf / mil.
[0116] The puncture fracture energy (ASTM D5748-19, using a 3 / 4 inch stainless steel uncoated probe and two 0.25 mil HDPE slides, machine model United SFM-1, test speed 10 in / min) can be in the range of 35 in*lbs / mil to 47 in*lbs / mil, or 35 in*lbs / mil to 42 in*lbs / mil, or 37 in*lbs / mil to 47 in*lbs / mil.
[0117] The haze (ASTM D1003-13) of blown films comprising the described polyethylene copolymers may range from 8.0% to 12.5%, or from 8.0% to 10.5%, or from 10.0% to 12.5%.
[0118] Polyethylene copolymer (or its blend) can be formed into monolayer or multilayer film.These films can be formed by any conventional technique, including extrusion, coextrusion, extrusion coating, lamination, blowing and casting, and the film can be obtained by flat film or tubular process, followed by orientation in the plane of the film in a uniaxial direction or in two mutually perpendicular directions.One or more layers of the film can be oriented in the horizontal and / or longitudinal direction to the same or different extent.The orientation can occur before or after the individual layers are combined.For example, the polyethylene copolymer (or its blend) layer can be extrusion coated or laminated to an oriented polypropylene layer or polyethylene copolymer (or its blend), and polypropylene can be coextruded into film together and then oriented.Similarly, the oriented polypropylene can be laminated to the oriented polyethylene copolymer (or its blend), or the oriented polyethylene copolymer (or its blend) can be coated on polypropylene and then optionally, the combination can be further oriented.
[0119] Films include monolayer or multilayer films. Specific end-use films include, for example, blown films, cast films, stretch films, stretch / cast films, stretch cling film, stretch hand wrap, machine stretch wrap, shrink film, shrink wrap, greenhouse film, laminates, and laminated films. Exemplary films are prepared by any conventional techniques known to those skilled in the art, such as techniques for preparing blown films, extruded films, and / or cast stretch films and / or shrink films (including shrink-on-shrink applications).
[0120] In one embodiment, the multilayer film (film of multiple layers) can be formed by any suitable method. The total thickness of the multilayer film can be changed based on the desired application. 5-100 μm, for example, a total film thickness of 10-50 μm is suitable for most applications. Those skilled in the art will appreciate that the thickness of the individual layers of the multilayer film can be adjusted based on the desired end-use performance, the polymer (one or more) used, the equipment capacity and other factors. The materials forming each layer can be coextruded by a coextrusion feedblock and a die assembly to produce a film with two or more layers bonded together but different in composition. Coextrusion can adapt to the use in both cast film and blown film processes. Exemplary multilayer films have at least two, at least three, or at least four layers. In one embodiment, the multilayer film consists of five to ten layers.
[0121] Specific applications of films comprising the polyethylene copolymers described herein may include trash bags, adult care products, agricultural films, aluminum foil laminates, aluminum laminates, asphalt films, automotive dashboard films, bacon packaging, bag-in-box liquid packaging applications, baked goods, banana films, tote bags, toilet paper overwrap, biaxially oriented films, biaxially oriented polypropylene (BOPP) films, cookie packaging, boutique bags, bread bags, bubble wrap, construction films, cake mix packaging, can liners, candy overwrap, paperboard liquid packaging, paving films, take-out bags, cement packaging, cereal liners, cheese packaging, chemical packaging, transparent films, coffee packaging, coin bags, collation shrink films, candy packaging, building panels, building films, consumer products, consumer trash bags, continuous wraps, simple packaging, cosmetic packaging, Counter bags, Cover films, Cupware / cutlery wrap, Delicatessen and bakery wrap, Detergent packaging, Diaper backing, Disposables (diapers, sanitary napkins, etc.), Dry food packaging, Dry grain, Air-filled bags, Fertilizer, Fish & Seafood packaging, Food packaging, Base films, Freeze dried products, Frozen films, Frozen food, Fruit juice packaging, Furniture bags, Gardening bags, Garment bags, Geomembrane liners, Gloves, Gravel bags, Greenhouse films, Grocery bags, Heavy duty bags, High clarity collation shrink films, High clarity films, High speed packaging applications, High stiffness overwrap films, Horizontal form fill and seal (HFFS) packaging, Household wrap, Hygienic overwrap films, Ice bags, Slit cloths, Industrial hardware packaging, Industrial liners, Industrial trash bags, Industrial spare parts packaging, In-store self-service bags, Insulated bags, Specialty liners (i nstitutional liner), juice bags, paper towels, garden bags, laminated films, light duty shrink films, lime bags, liners, liquid packaging, liquid and pellet food packaging, low stiffness overwrap films, magazine overwraps, mail bags, envelopes / bags, masking films, mayonnaise packaging, meat packaging, medical products, medical drapes, medium duty bags, commodity bags, metallized laminates, military equipment packaging, milk bags, milk powder packaging, atmosphere packaging, ground films, multi-wall bag liners, newspaper bags, nasal tissue wraps, olive oil packaging, bean packaging, cement products such as cement grout packaging, dry and sharp product packaging, pallet shrink film, pancake batter bags, paper handkerchief wraps, paper laminates, pasta overwraps, pelletized polymers, perfume packaging, personal care packaging, pesticide packaging, pharmaceutical packaging, pigment packaging, pizza packaging, polyamide laminates, polyester laminates, potato product packaging, soil bags for potting, small bags, poultry packaging, pre-made bags, fruit and vegetable bags, fruit and vegetable packaging, shelf and counter films, ready-made food packaging, ready-to-eat packaging, retort product packaging, rubber industrial films, sandwich bags, salt bags, sausage packaging, seafood packaging, bulk bags, shrink bags, shrink strapping films, shrink films, shrink covers, shrink trays, shrink wraps, snack food packaging, soft drink packaging, soil bags, soup packaging, condiment packaging, stand-up bags, storage bags, stretch film, stretch strapping, stretch wraps, supermarket bags, surgical gowns, take-away food bags, textile films, garbage bags, thermoformed containers, films, facial tissue wraps, tobacco packaging, tomato packaging,Ketchup packaging, trash bags, T-shirt bags, vacuum skin packaging, vegetable packaging, vertical form fill and seal (FFS) packaging, horizontal FFS packaging, tubular FFS packaging, and water bottle packaging.
[0122] In addition to films, the resin blends described herein will find utility in other applications such as, but not limited to, extrusion coating, injection molding, rotational molding, and blow molding applications.
[0123] Unless otherwise indicated, all numbers expressing quantities of ingredients, properties such as molecular weight, reaction conditions, etc. used in the present specification and the associated claims are to be understood as being modified in all instances by the term "about". Therefore, unless indicated to the contrary, the numerical parameters set forth in the following specification and the appended claims are approximations that may vary depending upon the desired properties sought to be obtained by a particular implementation of the present invention. At the very least, and not as an attempt to limit the application of the doctrine of equivalents to the scope of the claims, each numerical parameter should at least be construed based upon the number of reported significant digits and by applying ordinary rounding techniques.
[0124] This paper shows one or more illustrative specific implementations that incorporate one or more inventive elements. For the sake of clarity, not all entity implementation features are described or shown in this application. It should be understood that in the development of the entity implementation scheme that incorporates one or more elements of the present invention, many specific decisions to be implemented must be made to reach the developer's goal, such as meeting system-related, business-related, government-related and other restrictions, which vary from time to time with implementation. Although the developer's work can be time-consuming, such work will be a routine matter undertaken by those of ordinary skill in the art who benefit from the present disclosure.
[0125] Although compositions and methods are described herein in terms of "comprising" various components or steps, the compositions and methods may also "consist essentially of" or "consist of" the various components and methods.
[0126] Additional Implementations
[0127] Embodiment 1. A polyethylene copolymer comprising: ethylene units; and 0.1 mol% to 15 wt% of C3-C 18 α-olefin comonomer unit, the polyethylene copolymer has: 0.900 g / cm 3 Up to 0.915g / cm 3density, a melt index (MI, measured at 190°C and 2.16 kg load according to ASTM D1238-20) of 0.5 g / 10 min to 1.5 g / 10 min (I2), a melt index ratio of 15 to 40, a cross-fractionation chromatography (CFC) central cross moment covariance of less than -500 K (kg / mol), a CFC correlation of -0.3 or less, a CFC iso-half Tw1-Tw2 of -30°C or less and a Mw1 / Mw2 of 2 or greater, and a temperature rising elution fractionation (TREF) T75-T25 of 30°C to 36°C.
[0128] Embodiment 2. The polyethylene copolymer according to embodiment 1, wherein the polyethylene copolymer has a molecular weight of 0.900 g / cm 3 Up to 0.914g / cm 3 density.
[0129] Embodiment 3. The polyethylene copolymer according to embodiment 1 or embodiment 2, wherein the polyethylene copolymer has a molecular weight of 0.900 g / cm 3 Up to 0.912g / cm 3 density.
[0130] Embodiment 4. The polyethylene copolymer of any one of Embodiment 1 or Embodiments 2-3, wherein the polyethylene copolymer has a solubility distribution breadth index (SDBI) of 21.0°C to 25.0°C.
[0131] Embodiment 5. The polyethylene copolymer of any one of Embodiment 1 or Embodiments 2-4, wherein the polyethylene copolymer has short chain branching of 20 branches / 1000C to 25 branches / 1000C.
[0132] Embodiment 6. The polyethylene copolymer of any one of Embodiment 1 or Embodiments 2-5, wherein the polyethylene copolymer comprises 10 mol% to 15 mol% of C3-C18 α-olefin comonomer units.
[0133] Embodiment 7. The polyethylene copolymer of any one of Embodiment 1 or Embodiments 2-6, wherein the polyethylene copolymer has a Mw / Mn of 3.7 to 4.3.
[0134] Embodiment 8. A blown film comprising: a polyethylene copolymer comprising ethylene units; and 0.1 mol% to 15 wt% of a C3-C 18 α-olefin comonomer unit, the polyethylene copolymer has 0.900g / cm 3 Up to 0.915g / cm 3density, a melt index (MI, measured at 190°C and 2.16 kg load according to ASTM D1238-20) of 0.5 g / 10 min to 1.5 g / 10 min (I2), a melt index ratio of 15 to 40, a cross-fractionation chromatography (CFC) central cross moment covariance of less than -500 K (kg / mol), a CFC correlation of -0.3 or less, a CFC iso-half Tw1-Tw2 of 30°C or less and a Mw1 / Mw2 of 2 or greater, and a temperature rising elution fractionation (TREF) T75-T25 of 30°C to 36°C.
[0135] Embodiment 9. The blown film of embodiment 8, wherein the blown film has a seal initiation temperature of about 80°C or less.
[0136] Embodiment 10. The blown film of embodiment 8 or embodiment 9, wherein the blown film has a seal initiation temperature of about 75°C or less.
[0137] Embodiment 11. The blown film according to any one of Embodiment 8 or Embodiments 9-10, wherein the blown film has a maximum hot tack of 13 N / 25 mm or more.
[0138] Embodiment 12. The blown film according to any one of Embodiments 8 or 9-11, wherein the blown film has a maximum hot tack of 17 N / 25 mm to 22 N / 25 mm.
[0139] Embodiment 13. The blown film of any one of Embodiment 8 or Embodiments 9-12, wherein the blown film has a machine direction Elmendorf tear of 200 g / mil or greater.
[0140] Embodiment 14. The blown film of any one of Embodiment 8 or Embodiments 9-13, wherein the blown film has a machine direction Elmendorf tear of 250 g / mil or greater.
[0141] Embodiment 15. The blown film of any one of Embodiment 8 or Embodiments 9-14, wherein the blown film has a machine direction Elmendorf tear of 300 g / mil or greater.
[0142] Embodiment 16. The blown film of any one of Embodiment 8 or Embodiments 9-15, wherein the blown film has a dart drop of 500 g / mil to 1200 g / mil.
[0143] Embodiment 17. The blown film of any one of Embodiment 8 or Embodiments 9-16, wherein the blown film has a puncture peak force of 10.5 lbf / mil to 14.0 lbf / mil.
[0144] Embodiment 18. The blown film of any one of Embodiment 8 or Embodiments 9-17, wherein the blown film has a puncture energy to break of 35 in*lbs / mil to 47 in*lbs / mil.
[0145] In order to facilitate a better understanding of the embodiments of the present invention, the following examples of preferred or representative embodiments are provided. The following examples should in no way be construed as limiting or defining the scope of the invention.
[0146] Example
[0147] Several mLLDPE samples (inventive samples I1-I6) were synthesized using Hf-metallocene catalysts according to Table 1. Comparative samples C7-C17 are commercially available samples listed in Table 2. The properties of inventive samples I1-I6 and comparative samples C7-C17 are provided in Tables 3A-3C. The figure is a plot of (Mwl / Mw2) (logarithmic scale) versus (Twl-Tw2) for inventive and comparative samples.
[0148] Table 1
[0149]
[0150] Table 2
[0151]
[0152]
[0153] Table 3A
[0154]
[0155]
[0156] Table 3B
[0157] nature C7 C8 C9 C10 C11 <![CDATA[Density (g / cm 3 )]]> 0.914 0.909 0.912 0.912 0.919 I2(g / 10min) 0.83 1.9 1.01 1.98 0.99 I21(g / 10min) 24.5 30.9 16.5 32.6 15.24 MIR(I21 / I2) 29.54 16.26 16.31 16.44 15.39 Mn(g / mol) 29655 35600 43229 36090 40273 Mw(g / mol) 120802 90707 108179 90936 108697 Mz(g / mol) 303057 161728 194122 162067 198185 Mw / Mn 4.07 2.55 2.5 2.52 2.7 Comonomer Hexene Hexene Hexene Hexene Hexene % comonomer (mol%) 10.11 11.61 9.34 10.01 6.28 CDBI(%) 42.76 77.41 74.43 74.71 59.73 SDBI(℃) 20.2 19.6 20.4 20.7 22.5 T75-T25(℃) 27.6 15.9 13.5 14.1 11.6 Tw1(℃) 57.7 57.3 66.6 64.1 77.6 Tw2(℃) 87.0 77.6 83.8 82.4 88.8 Tw1-Tw2(℃) -29.3 -20.2 -17.2 -18.3 -11.2 Mw1 / Mw2 2.72 1.00 1.02 0.98 1.13 Covariance (K*(kg / mol)) -1139.0 46.0 45.0 86.0 18.0 Relevance -0.31 0.02 0.03 0.06 0.01 SCB (branch / 1000C) 19.9 22.6 17.0 19.1 12.7 η*at 0.01rad / sec and 190℃(Pa*s) 10611 3940 7133 3772 7472 η*at 100rad / sec and 190℃(Pa*s) 1887 1797 2489 1799 2661 η* at 0.01 divided by η* at 100 6 2 3 2 3
[0158] Table 3C
[0159]
[0160]
[0161] N / A means not measured
[0162] Using a blown film line, the sample was formed into a film using a die diameter of 160 mm, a blow-up ratio (BUR) of 2.5: 1, and a die temperature of about 390 ° F to about 410 ° F. The film was made using a die gap of 90 mil (E1-E6 and C7) or 60 mil (C8-C12 and C14-C15), a line speed of about 240 ft / min to about 250 ft / min (E1-E6, C7 C9, C11, C12) or about 220 ft / min (C8, C10, C14, C15), a die coefficient of 15 lb / hr / (in die circumference) (E1-6 and C7, C9, C11, and C11-C12) or about 13 lb / hr / (in die circumference) (C8, C10, and C14-C15). Film properties are provided in Tables 4A-4C.
[0163] Table 4A
[0164]
[0165]
[0166]
[0167] Table 4B
[0168] nature C7 C8 C9 C10 C11 Film thickness(mil) 1 1 1 1 1 1% Secant MD(psi) 21776 11900 16068 14200 23,749 1% Secant TD(psi) 26896 12200 17377 14700 25,996 Yield Strength MD(psi) 1174 820 975 920 1,313 Yield Strength TD(psi) 1229 780 914 910 1,398 Yield elongation MD (%) 6.47 8.2 7.4 7.6 7.4 Yield elongation TD (%) 6.00 7.9 6.5 9.3 8.5 Tensile strength at break MD(psi) 8847 10650 10622 10350 10034 Tensile strength at break TD(psi) 8537 9780 9217 8460 9131 Elongation at break MD (%) 337 507 454 531 492 Elongation at break TD (%) 599 604 641 619 678 Elmendorf Tear MD (g / mil) 231 222.6 209 249.3 273 Elmendorf Tear TD (g / mil) 372 283.4 329 315.9 410 Elmendorf tear MD(kN / m) 90.7 87.3 81.9 97.7 107.0 Elmendorf tear TD(kN / m) 145.6 111.1 129.0 123.8 160.7 Haze(%) 9.9 27.5 8.3 >30 17.1 Glossiness MD(GU) 48 21.2 61 19 37 Gloss TD(GU) 48 20.6 60 16.9 40 Dart Phenolic Resin Method A (g) 889 693 1070 927 830 Dart Phenolic Resin Method A (g / mil) 896 N / A 1103 N / A 865 Dart Phenolic Resin Method A (kN / m) 351 N / A 432 N / A 339 Peak puncture force (lbf) 11.82 13.4 15.36 13 13.42 Peak puncture force / mil (lbf / mil) 11.92 13.8 15.83 13.6 13.98 Puncture breaking energy (in*lbs) 38.96 46.1 51.38 46.9 44.49 Puncture breaking energy / mil(in*lbs / mil) 39.27 47.3 52.97 49.2 46.35 Maximum hot bonding force (N / 25mm) 14.1 8.4 15.6 10.8 14.7 Sealing start temperature (℃) 85 75 85 85 100 Hot sticking starting temperature (℃) 95 80 100 95 105
[0169] Table 4C
[0170]
[0171]
[0172] Therefore, the present disclosure is well suited to achieve the objects and advantages mentioned and those inherent therein. The specific embodiments disclosed above are illustrative only, because the present disclosure can be modified and practiced in different but equivalent ways that are obvious to those of ordinary skill in the art who benefit from the teachings herein. In addition, except as described in the claims below, it is not intended to limit the details of the construction or design shown herein. It is therefore obvious that the specific illustrative embodiments disclosed above can be modified, combined or modified and all such changes are considered to be within the scope and spirit of the present invention. The invention disclosed illustratively herein can be appropriately practiced in the absence of any element not specifically disclosed herein and / or any optional element disclosed herein. Although the compositions and methods are described in terms of "comprising", "containing", or "including" various components or steps, the compositions and methods can also be "essentially composed of" or "composed of" various components and methods. All numerical values and ranges disclosed above can be changed by a certain amount. Whenever a numerical range with a lower limit and an upper limit is disclosed, any number and any included range falling within the range are specifically disclosed. In particular, each range of values disclosed herein (of the form "about a to about b" or equivalently "about a to b" or equivalently "about ab") should be understood to list every number and range encompassed within the broader range of the stated values. Furthermore, unless otherwise clearly and unambiguously defined by the patentee, the terms in the claims have their plain, ordinary meaning. Furthermore, the indefinite articles "a" or "an", as used in the claims, are defined herein to mean one or more than one of the elements they introduce.
Claims
1. Polyethylene copolymer, comprising: Ethylene units; and 0.1 mol% to 15 wt% C3-C 18 α-olefin comonomer units, the polyethylene copolymer has: 0.900g / cm 3 Up to 0.915g / cm 3 The density of 0.5 g / 10 min to 1.5 g / 10 min melt index (MI, measured according to ASTM D1238-20 at 190° C. and 2.16 kg load) (I2), Melt index ratio of 15 to 40, The cross-fractionation chromatography (CFC) central cross moment covariance less than -500K (kg / mol), CFC correlation of -0.3 or less, -30℃ or less CFC etc. half Tw1-Tw2 and 2 or more Mw1 / Mw2, and Temperature Rising Elution Fractionation (TREF) T75-T25 from 30°C to 36°C.
2. The polyethylene copolymer according to claim 1, wherein the polyethylene copolymer has a 3 Up to 0.914g / cm 3 density.
3. The polyethylene copolymer according to claim 1, wherein the polyethylene copolymer has a 3 Up to 0.912g / cm 3 density.
4. The polyethylene copolymer of claim 1, wherein the polyethylene copolymer has a solubility distribution breadth index (SDBI) of 21.0°C to 25.0°C.
5. The polyethylene copolymer of claim 1, wherein the polyethylene copolymer has short chain branching of 20 branches / 1000C to 25 branches / 1000C.
6. The polyethylene copolymer of claim 1, wherein the polyethylene copolymer comprises 10 to 15 mol% of C3-C18 α-olefin comonomer units.
7. The polyethylene copolymer of claim 1, wherein the polyethylene copolymer has a Mw / Mn of 3.7 to 4.
3.
8. Blown film, including: Polyethylene copolymers comprising: Ethylene units; and 0.1 mol% to 15 wt% C3-C 18 α-olefin comonomer units, the polyethylene copolymer has: 0.900g / cm 3 Up to 0.915g / cm 3 The density of 0.5 g / 10 min to 1.5 g / 10 min melt index (MI, measured according to ASTM D1238-20 at 190° C. and 2.16 kg load) (I2), Melt index ratio of 15 to 40, The cross-fractionation chromatography (CFC) central cross moment covariance less than -500K (kg / mol), CFC correlation of -0.3 or less, 30℃ or less CFC etc. half Tw1-Tw2 and 2 or more Mw1 / Mw2, and Temperature Rising Elution Fractionation (TREF) T75-T25 from 30°C to 36°C.
9. The blown film according to claim 8, wherein the blown film has one or more of the following properties: (a) a seal initiation temperature of about 80°C or less; (b) a maximum hot tack force of 13 N / 25 mm or greater; (c) a longitudinal Elmendorf tear (MD Elmendorf tear) of 200 g / mil or greater; (d) 500 g / mil to 1200 g / mil darts; (e) a peak puncture force of 10.5 lbf / mil to 14.0 lbf / mil; and (f) Puncture breaking energy of 35 in*lbs / mil to 47 in*lbs / mil.
10. The blown film of claim 9 having all of properties (a) to (f).
11. The blown film according to claim 9, wherein the seal initiation temperature of the blown film is 75°C or less; and / or wherein the blown film has a maximum hot tack of 17 N / 25 mm to 22 N / 25 mm.
12. The blown film of claim 9, wherein the blown film has an MD Elmendorf Tear of 250 g / mil or greater.
13. The blown film of claim 12, wherein the blown film has an MD Elmendorf Tear of 300 g / mil or greater.
Citation Information
Patent Citations
Method for determining a stickiness temperature of a resin
US10029226B2
Metallocene-produced polyethylene for glossy plastic containers
US20040121098A1
Linear low density polymer blends and articles made therefrom
US20070260016A1
Matte finish polymide films and methods relating thereto
US20130266789A1
Ethylene-Based Polymers and Articles Made Therefrom
US20150232589A1